'Complete freedom to choose within limits' – teachers' views of curricular autonomy, agency and control in Estonia, Finland and Germany. Issue 2 (3rd April 2018) - Erss, Maria
ABSTRACT: To examine different approaches to teacher autonomy in nation‐states, three countries were selected for a comparative study: Estonia, Finland and Germany. The emphasis of the study lies on the subjective perceptions of upper secondary school teachers ( n = 33 semi‐structured interviews) regarding their curricular autonomy and experiences of being controlled by the system. The article discusses different concepts of teacher autonomy and agency theoretically and concludes that they are partly overlapping, but not the same. Agency can be understood as the realistic actualization of autonomy within the constraints of the teaching profession, while autonomy is, in theory, more liberating, focusing on self‐directedness, capacity for autonomous action and freedom from control. The data analysis showed that the expectations of teachers as to the amount of desired autonomy varied greatly. While the Finnish teachers in the study perceived control over teachers' work to be unnecessary, due to their high professionalism, the Estonian and German teachers did not advocate absence of control, instead preferring to 'have complete freedom to choose within limits.'